The battle for sabarimala: Religion, law, and gender in contemporary India - Acevedo, deepa das (New Delhi Oxford university press, 2023)
The Battle for Sabarimala' tells the story of one of contemporary India's most contentious disputes: a long-running struggle over women's access to the Hindu temple at Sabarimala
Keywords: Women's rights India; Religion and law; Women Religious aspects Hinduism